Generalized contraction mapping in probabilistic metric space - Rahman, Shams-ur; Jha, K (Kathmandu University Journal of Science Engineering and Technology, 2011)
The probabilistic metric space as one of the important generalization of metric space was introduced by K. Menger in 1942. In this paper, we briefly discuss the historical developments of contraction mappings in probabilistic metric space with some fixed point results.